Single dose antidepressant administration modulates the neural processing of self-referent personality trait words. - Miskowiak, K; Papadatou-Pastou, M; Cowen, P; Goodwin, G; Norbury, R; Harmer, C (2007)
Drugs which inhibit the re-uptake of monoamines in the brain are effective in the treatment of depression; however, the neuropsychological mechanisms which lead to the resolution of depressive symptomatology are unclear. Behavioral studies in healthy volunteers suggest that acute administration of the selective norepinephrine reuptake inhibitor reboxetine modulates emotional processing. The current study therefore explored the neural basis of this effect. A single dose of reboxetine (4 mg) or placebo was administered to 24 healthy volunteers in a double-blind between-group design. Neural responses during categorisation and recognition of self-referent personality trait words were assessed using event-related functional Magnetic Resonance Imaging (fMRI). Reboxetine had no effect on neuronal response during self-referent categorisation of positive or negative personality trait words. However, in a subsequent memory test, reboxetine reduced neuronal activation in a fronto-parietal network during correct recognition of positive target words vs. matched distractors. This was combined with increased speed to recognize positive vs. negative words compared to control subjects and suggests facilitated memory for positive self-referent material. These results support the hypothesis that antidepressants have early effects on the neural processing of emotional material which may be important in their therapeutic actions.